Pipeline Populism : Grassroots Environmentalism in the Twenty-First Century - Bosworth, Kai, 1987- (Book collections on Project MUSE., 2022)
"Kai Bosworth reveals the complex role populism has played in shifting interpretations of environmental movements, democratic ideals, scientific expertise, and international geopolitics. Probing the very limits of populism, Pipeline Populism presents essential work for an era defined by a wave of people-powered movements around the world"--